Model Arsitektur Smart Library di Perguruan Tinggi Se-Kota Batam - Holong Marisi Simalango; Muhammad Khaerul Naim Mursalim (Politeknik Negeri Batam, 2019)
Design of smart library architecture model is a new architectural model of integrating library information systems in several universities that still use WebApp but are local, so that it is expected to be connected to the new architectural design. The design of this model focuses on the use of web services, the application of the concept of Open access by utilizing QR Code as an Internet of Things (IoT). This design focuses on the technology that will be used to integrate library information systems in all universities, especially in the city of Batam. Object Oriented Analysis (OOA) is a methodology used in designing smart library architecture models and using Unified Modeling Language (UML). Architectural design consists of business architecture, information architecture, and technology architecture. Business architecture design modeling is described in the business use case explaining the actors namely students and library staff as well. The results of the design of the smart library architecture model are in the form of design recommendations for the construction of smart libraries at universities in the city of Batam. The design of this smart library architecture model with the application of technological trends will provide convenience and support to the academic community in the use of library systems.